SEMINAR ANTIBAKTERI EKSTRAK ETANOL DAUN PACAR AIR (Impatiens balsamina L.) TERHADAP BAKTERI Propionibacterium acne - Debi Dinha Octora; Asti Pratiwi; Krismawati Waruwu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
The antibacterial activity of Impatiens balsamina L. has been studied for many years. Water henna leaves contain flavonoids, saponins and tannins which have the ability to inhibit bacterial growth. P. acnes is one type of bacteria that can cause infection in acne. One of the objectives of this study was to determine the antibacterial activity of the ethanol extract of henna water leaves and the most effective concentration in inhibiting P. acnes bacteria. This research is a pure experimental research. Water henna leaves were macerated with 96% ethanol as solvent. Antibacterial activity test was carried out by disc diffusion method. The research was conducted with 3 different concentration variations. The results showed that there was antibacterial activity at each concentration. The conclusion is that the ethanol extract of henna leaves with concentrations of 25%, 50% and 75% gave the most effective bacterial growth inhibition with concentrations of 25%, 50% and 75% which were included in the strong category.